(untitled) (Development Service Industry Management, 2025)
In the context of modern challenges related to globalisation, rapid and large-scale changes in lifestyles, urbanisation, political and economic instability and, accordingly, a significant increase in stress levels, especially in countries at war, the problem of preserving mental health is becoming increasingly important. Researching the impact of tourism on mental health (including the historical context) in order to further use the knowledge gained to ensure the overall well-being of people is particularly important for Ukraine, whose population has been under martial law for three years. Thanks to its diversity of products and integrated approach, tourism uses the available means as an effective complement to traditional psychotherapy methods, providing people with new opportunities for healing and growth. The article examines the impact of travel on a person’s mental health using the biographical method (on the example of Alienora of Aquitaine, Danylo Palomnyk and Lesya Ukrainka) and determines whether these individuals belong to a certain type of traveller according to Stanley Plog’s psychographic model. The study focuses on the peculiarities of travel, its motives, reflection, and the impact of changing locations on physical, mental, and psychological health. The study once again emphasises the effectiveness of using tourism to improve mental health, as travel generates powerful emotions, shapes a person’s worldview, character, intelligence, including emotional intelligence, enhances the cognitive capabilities of the brain, facilitates recovery from stress, forms social connections (according to modern Harvard University researchers, they are the most important factor in happiness), and creates many new opportunities for people to enjoy life. This is a particularly important task for Ukraine in the wartime and post-war periods, given the need for psychological rehabilitation of civilians and war veterans, as well as the country’s strong tourism potential.